2011
DOI: 10.1111/j.1440-1746.2011.06747.x
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy of endoscopic ultrasound‐guided fine needle aspiration for suspected pancreatic malignancy in relation to the size of lesions

Abstract: EUS-FNA was accurate in the evaluation of suspected pancreatic malignancy regardless of its size, location, or size of needles. It was useful also in the confirmation of small pancreatic malignancies less than 10mm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
92
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(95 citation statements)
references
References 27 publications
0
92
0
3
Order By: Relevance
“…A 25-gauge needle is therefore recommended to puncture the head of the pancreas 4 . Several studies have compared the performance characteristics of a 22-gauge needle with those of a 25-gauge FNA needle for sampling pancreatic masses, but most have failed to demonstrate superiority of either needle [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] . A recent systematic review and meta-analysis of EUS-FNA for solid pancreatic masses, including a large cohort of patients, revealed that a 25-gauge needle was more sensitive than a 22-gauge needle 23 .…”
Section: Discussionmentioning
confidence: 99%
“…A 25-gauge needle is therefore recommended to puncture the head of the pancreas 4 . Several studies have compared the performance characteristics of a 22-gauge needle with those of a 25-gauge FNA needle for sampling pancreatic masses, but most have failed to demonstrate superiority of either needle [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] . A recent systematic review and meta-analysis of EUS-FNA for solid pancreatic masses, including a large cohort of patients, revealed that a 25-gauge needle was more sensitive than a 22-gauge needle 23 .…”
Section: Discussionmentioning
confidence: 99%
“…EUS combined with FNA (EUS-FNA) has been demonstrated to be more accurate in diagnosing solid pancreatic lesions and has gained wide acceptance [7]. However, the reported sensitivity and specificity of EUS-FNA vary greatly across studies (sensitivity: 73.20–96.50 %; specificity: 71.40–100 %) [726]. In addition, the majority of previous studies were dependent on single-center trials.…”
Section: Introductionmentioning
confidence: 99%
“…Repeat biopsies raise the costs of diagnosis and constitutively require extra patient discomfort. Several studies have established the benefits of on-site evaluation of adequacy (OSEA) for enhancing the diagnostic yield of the pancreatic FNA procedure [7,8,9,10,11,12]. When viewed on the scale of a large institution, these benefits also translate into cost savings [13,14].…”
Section: Introductionmentioning
confidence: 99%